Adaptive Noise Cancellation Using Bio-Inspired Algorithm - T. Suman; G. Akshaya; E. Hemalalitha; M. Anusha; Shaik Alisha (Journal of Electronic Design Engineering, 2023)
The advancement of science and technology has led to an increase in acoustic noise problems in our daily lives, caused by the operation of mechanical machines in household tasks, industries, and other areas in present scenarios. Adaptive Noise Control (ANC) System is introduced as a solution to decrease the amount of acoustic noise, which has attracted many researchers. In this paper, a Bio-inspired algorithm is employed for the implementation of an ANC System to reduce acoustic noise. The proposed bio-inspired algorithm combines with adaptive algorithms to perform the ANC system. This paper presents an alternate approach where the adaptive algorithm is substituted with a genetic algorithm to decrease the noise and improve the speed of an ANC system. The computational complexity and convergence are analyzed. Evaluations are performed on the ANC system with random noise, colour noise and different recorded noise signals that are obtained.